Calciphylaxis: a rare but potentially fatal event of chronic kidney disease. Case report - Silvio Alencar Marques; Aline Cruz Kakuda; Thais Jung Mendaçolli; Luciana P. Fernandes Abbade; Mariângela Esther Alencar Marques (Sociedade Brasileira de Dermatologia, 2013)
Calciphylaxis or calcific uremic arteriolopathy is a rare cutaneous-systemic disease occurring in patients with advanced chronic kidney disease. The classical clinical picture is that of a necrotic and progressive skin ulcer of reticular pattern, mostly in the lower legs and susceptible to local infection. It is a product of mural calcification and occlusion of cutaneous and sub-cutaneous arteries and arterioles. The authors report the case of a 73-year-old male patient in his late stage of renal disease presenting severe necrotic cutaneous ulcers on lower legs followed by local and systemic infection and death due to sepse after parathyroidectomy.